Weathering the storm of emotions: immediate and lasting effects of reinterpretation and distancing on event-related potentials and their association with habitual use of cognitive reappraisal - Zehtner, Raphaela I.; Neudert, Marie K.; Schäfer, Axel; Fricke, Susanne; Seinsche, Rosa J.; Stark, Rudolf; Hermann, Andrea; Justus Liebig University Giessen (My University, 2023)
Reinterpretation and distancing, two cognitive reappraisal tactics, are known to effectively reduce negative feelings and event-related potentials (ERPs), such as the P300 and the late positive potential (LPP), in the short-term. Less is known about differential and lasting effects on ERPs as well as their association with habitual reappraisal. Fifty-seven participants were instructed to passively view or reappraise (reinterpretation, distancing) pictures that were repeatedly presented with the same instruction (active regulation phase). Thirty minutes later, these pictures were shown again without instruction for the assessment of lasting effects (re-exposure phase). ERPs were recorded and participants rated the intensity of negative feelings following picture presentation. Reappraisal led to an attenuation of the LPP, and both tactics decreased negative feelings during active regulation, whereby reinterpretation had a stronger impact on the subjective level. Passive re-exposure resulted in reduced negative feelings for previously reappraised pictures but had no lasting effects on ERPs. Higher habitual reappraisal was associated with higher P300 and early LPP amplitudes for emotional reactivity during the active regulation phase. During the re-exposure phase, higher habitual reappraisal was not related to ERPs. The current findings emphasize the effectiveness of both tactics in the short-term and lasting effects on the subjective experience of negative feelings. Enhanced emotional reactivity on the electrocortical level in individuals with a more frequent habitual use of reappraisal might indicate a higher preparedness to regulate.
Keywords: ddc:150